Validation of Daylight Analysis Methodology Using Field Measurements and a Simulation Model - A Case Study of Residential Building in Nagpur - Dabe, Trupti J.; Dongre, Alpana R. (New Ideas Concerning Science and Technology Vol. 11, 2021)
Use of natural daylight in the building is energy saving with respect to illumination levels and health benefits. However, in the hot and dry climatic zone increase in daylight availability may result into thermal ingress. This might lead to excess energy consumption. The aim of this paper is to evolve the methodology which could be used as a pre-design tool for assessing the daylighting provisions and thermal performance of spaces within buildings adopted by designers during the design process. A liveable space of a dwelling unit of Nagpur is taken up as the case study. The methodology, focused on comparision of field measurements have been compared with the simulation model. This model can be used for further evaluation of daylight parameters has been worked out. The field measurements, are conducted for both daylight levels and thermal energy. The field measurements are taken with the help of sensors and simulation by using Ecotect Analysis 2011 software. The percentage difference (PD) between simulation (S) and the field measurements (FM) for a daylight level if less than 15%, the simulated model is considered accurate for further study of evaluation of selected parameters. The result shows that the simulated model would be ample for designers to evaluate the parameters with respect to the orientation of the building which helps to achieve the optimum daylight level into the interior spaces of the building.